Timely Supplementation of Hydrogels Containing Sulfated or Unsulfated Chondroitin and Hyaluronic Acid Affects Mesenchymal Stromal Cells Commitment Toward Chondrogenic Differentiation - Alessio, Nicola; Stellavato, Antonietta; Aprile, Domenico; Cimini, Donatella; Vassallo, Valentina; Di Bernardo, Giovanni; Galderisi, Umberto; Schiraldi, Chiara (Frontiers in Cell and Developmental Biology, 2021)
Mesenchymal stromal cells (MSCs) are currently used for cartilage cell therapy because of their well proven capacity to differentiate in chondrocytes. The advantage of MSC-based therapy is the possibility of producing a high number of chondrocytes for implants. The transplant procedure, however, has some limitations, since MSCs may produce nonfunctional chondrocytes. This limit has been challenged by cultivating MSC in media with hydrogels containing hyaluronic acid (HA), extractive chondroitin sulfate (CS) or bio-fermentative chondroitin (BC) alone or in combination. Nevertheless, a clear study of the effect of glycosaminoglycans (GAGs) on chondrocyte differentiation is still lacking, especially for the newly obtained unsulfated chondroitin of biotechnological origin. Are these GAGs playing a role in the commitment of stem cells to chondrocyte progenitors and in the differentiation of progenitors to mature chondrocytes? Alternatively, do they have a role only in one of these biological processes? We evaluated the role of HA, CS, and – above all – BC in cell commitment and chondrocyte differentiation of MSCs by supplementing these GAGs in different phases of in vitro cultivation. Our data provided evidence that a combination of HA and CS or of HA and BC supplemented during the terminal in vitro differentiation and not during cell commitment of MSCs improved chondrocytes differentiation without the presence of fibrosis (reduced expression of Type I collagen). This result suggests that a careful evaluation of extracellular cues for chondrocyte differentiation is fundamental to obtaining a proper maturation process.